Short-Term Hydrothermal Scheduling using Imperialist Competitive Algorithm (ELEKTRIKA- Journal of Electrical Engineering, 2021)
In this study, the Imperialist Competitive Algorithm (ICA) is proposed to solve a multi-chain Short-Term Hydrothermal Scheduling problem (STHTS). It aims to minimize the generation cost of the thermal plants while satisfying the thermal and hydro plants constraints. In order to evaluate the effectiveness of the ICA, it has been tested on a system having a hydro plant with four-cascaded reservoir and a thermal plant. The results are compared with that obtained by other techniques. The ICA has the good convergence and the better results.
Keywords: Imperialist Competitive Algorithm; Short-Term Hydrothermal Scheduling